BUSINESS ETHICS FROM AN ISLAMIC PERSPECTIVE: A QUALITATIVE STUDY OF TRADITIONAL MARKET TRADE IN BONDOWOSO CITY - Romadhoni, Riyan (Media Inovasi Pendidikan dan Publikasi, 2025)
Business ethics in Islam extends beyond economic principles to encompass moral and spiritual aspects. Principles such as honesty, fairness, and social responsibility are essential foundations for Sharia-compliant trading activities. The purpose of this study is to describe the understanding and implementation of business ethics from an Islamic perspective among traditional market traders in Bondowoso City. A qualitative case study approach was used to gather information from business actors through in-depth interviews, direct observation, and document collection. The results indicate that most traders understand and respect Islamic principles in business. However, in practice, deviations persist due to economic pressures, business competition, and a lack of guidance from authorities. The findings of this study are expected to serve as a reference in designing policies and training programs on Islamic business ethics to encourage the development of fair, ethical, and sustainable traditional markets.